Design and process optimization of a new reaction chamber for microwave synthesis of MOFs materials - Jiadai An; Xianying Dai; Ying Liu; Kama Huang; Dengke Zhang (Heliyon)
Based on the application demand of metal-organic framework (MOFs) materials in environmental science, energy conversion, biomedicine and other fields, its efficient synthesis method has attracted much attention. Microwave method has become one of the most competitive and potential methods because of its low cost, high efficiency and green environmental protection. However, the traditional microwave assisted synthesis of MOFs materials mostly uses microwave oven as the reaction chamber, or small-scale microwave reactor. There are many problems such as uneven heating, low microwave utilization rate and low one-time synthesis yield. In view of the above problems, the design and process optimization of a new type reaction chamber for microwave synthesis of MOFs materials were studied in this paper. A material synthesis reactor using waveguide as microwave source was designed. The structure model of the reactor was optimized by multi-physics numerical simulation, and better heating uniformity and microwave utilization were obtained. At the same time, the optimization test of key process parameters was designed by orthogonal method, and the optimal process parameter combination of this model for the synthesis of MOFs materials was obtained: microwave power is 200 W, irradiation time is 100 min, and reagent concentration is 50 mM/L. This study will promote the microwave method to achieve more efficient and uniform MOFs material synthesis, which is of great significance for further improving material yield and properties and industrial practical applications.